Penerapan Agroteknologi Konservasi dalam Usahatani Kentang di Desa Kebun Baru, Kecamatan Kayu Aro Barat, Kabupaten Kerinci - Henny H.; Neliyati Neliyati; Zulkarnain Zulkarnain; Sunarti Sunarti (Departemen Budidaya Tanaman Perkebunan, Fakultas Pertanian, Universitas Andalas, 2026)
Vegetable farming in Kayu Aro Barat District is generally on sloping land with Andisol soil which is sensitive to erosion and high P retention by amorphous minerals and Al-humus. However, farmers plant potatoes as the main commodity with ridges along the slope, excessive chemical fertilizers, especially P, and without adequate organic fertilizers with relatively low productivity. Community service activities in partnership with the G7 Farmers Group and the Arimbi Women's Farmers Group in Kebun Baru Village introduced